Theologi pada Toponimi Nama-Nama Kampung di Kecamatan Jatiasih, Kota Bekasi: Kajian Filsafat Antropolinguistik - Ahmad Khoiril Anam; Zuryati Zuryati; Saifur Rohman (LITERATUS, 2022)
The purpose of this study is to describe in depth the theological elements in the origin of village names in Jatiasih District, Bekasi City. The method used in this research is descriptive using a qualitative approach. The object of this research includes the names of villages in Jatiasih District, Bekasi City. Based on the data analysis, the author can conclude: there are five of the eleven villages whose toponyms or the origins of the naming of the village are motivated by theological values ??in it. The five names of the villages are Kebantenan Village, Pamahan Village, Pondok Benda Village, Bojong Sari Village, and Jatikramat Village. The overall theological value in naming the village names is based on the relationship between the two great Islamic empires on the island of Java, namely the Cirebon Kingdom and the Banten Kingdom. All stages of theology adopted in the formation of the names/toponyms of the five villages in Jatiasih are the stages of dynamism originating from tombs, people, to sacred trees. Historically, the theological value presented is more about the story of the spread of Islam carried out by religious leaders from the two kingdoms who often stop in the villages in Jatiasih.